Morphological Characterization and Toxigenicity Screening of Aspergillus flavus Isolated from Maize in Pakistan (Plant Bulletin, 2025)
Aflatoxin contamination of maize is a major problem in Pakistan, posing a threat to food safety and human health. This study aims to characterize Aspergillus flavus isolates from maize samples collected from different locations in Punjab on the basis of morphology. Screening of aflatoxigenic and non-aflatoxigenic isolates was also one of the objectives of this study. Maize samples were cultured on potato dextrose agar (PDA) and pure cultures were sub-cultured onto four differential media to identify the isolates using macro- and micro-morphological characteristics. Differential media included were Malt Extract Agar (MEA), Czapek Dox Agar (CZA), Modified Rose Bengal Agar (RBA), and Aspergillus flavus parasiticus Agar (AFPA). These specialized media enable species identification based on macro-morphological characteristics. The isolates were then cultivated on Coconut Agar Media (CAM) and Yeast Extract Sucrose media (YES) to determine their aflatoxin-producing potential based on ammonia vapor test focusing on reverse colony color changes. This study provided valuable information on the prevalence of aflatoxin-producing A. flavus isolates in maize in four districts of Punjab, Pakistan. The study contributes to developing early detection and management techniques for aflatoxin contamination. Our research aims to maintain the economic value of this important staple crop while substantially contributing to improving food safety and security in Pakistan. Further significance of the findings has been discussed.
Keywords: Aspergillus flavus, aflatoxins, morphology, aflatoxin profiling, maize, nutrient media